Current relevance : a cognitive account - Stanojević, Mateusz-Milan (2004)
Katičić's syntax of Croatian analyzes the Croatian perfekt tense as expressing the complete (Croatian: gotov) and incomplete (Croatian: negotov) present (Katičić 1991:50, 53 ; Barić et al. 1995:406 ff.). The complete present, according to Katičić, is connected to a given moment by the consequences of the action, and not by the action itself. In the analysis of the English present perfect a similar notion is expressed by "current relevance" (see e.g. Comrie 1985: 25 ; Palmer 1987:48-51 ; Langacker 1991: 211-215). However, in Croatian, the current relevance of the perfekt tense can also be "neutralized" (Katičić 1991: 53), that is the perfekt tense does not necessarily have to be connected to the present consequences of the action. Current relevance is not grammatically encoded, but can only be recovered from the context. Therefore, the question arises whether it is necessary to introduce it into the analysis of the perfekt. The authors will re-analyze the Croatian perfekt tense and the notion of current relevance in terms of Langackerian cognitive grammar (Langacker 1990 ; Langacker 1991) and Fauconnier's mental spaces (Fauconnier 1997) in an attempt to prove that the prototypical value of the perfekt is vague with regard to completeness. On the basis of this, the Croatian perfekt tense and the English present perfect will be contrasted, and certain theoretical consequences for the teaching of the English present perfect to Croatian speakers will be drawn.